The Influence of Regional Revenue and Expenditure Budget (APBD) Management Competency in the Gorontalo City Library and Archives Service - Misna Usman; Talalu , Mohammad Abubakar; Pariyono, Agus (Indonesian Journal of Advanced Research, 2023)
The aim to be achieved in this research is to determine and analyze the influence of competence on the management of regional revenue and expenditure budgets (APBD) in the Gorontalo City Library and Archives Service. The location of this research was carried out at the Gorontalo City Library and Archives Service. The type of research used is survey research. This research consists of two variables related to competency, namely variable Which consists of 21 civil servants and 17 contract workers. Data Collection Techniques through Observation, Questionnaires, Documentation. Sugiyono (2018:112) Quantitative analysis of data testing through requirements consisting of: 1) Looking for Linear Regression Equations 2) Looking for Correlation Coefficients 3) Testing the Significance of Correlation. The research results show that competency has a positive and significant influence on APBD management. Adequate competency will increase the effectiveness of APBD management. The results of the research hypothesis test found that the form of the simple linear regression equation obtained was . and the correlation coefficient is 0.723 and the coefficient of determination is 0.522. This means that competence contributes 52.2% to APBD management, and the remaining 47.8% is determined by other factors including responsibility and work motivation.